PERANCANGAN SISTEM INFORMASI SURAT MENYURAT BERBASIS WEB (STUDI KASUS : DMPTPSP KABUPATEN MUARO JAMBI ) - Lisdarti, Lisdarti; Hendriansyah, Randi (JURNAL AKADEMIKA, 2024)
Information systems are one of the most important needs of society in the current era of globalization. One important aspect that is needed especially in the field of education is school. The implementation of information systems in schools can also help schools produce accurate, timely and relevant information. At the DPMPTSP Office of Muaro Jambi Regency, there is an activity called archiving. In this archive management activity, the DPMPTSP Office of Muaro Jambi Regency still uses a manual system in registering students which results in the performance of the school being less effective. The implementation of the street vendor system aims to build a system that can facilitate the management archive at DPMPTSP Office of Muaro Jambi Regency. This research was conducted using a responsive Web. By using the PHP programming language and MySQL database where the authors carry out system development with design, UML (Unified Modeling Language), which can provide users with visual or image modeling languages of various types of programming and general engineering processes. Brings together the best information available in modeling, table design, and interface design. This system displays class data, department data, year data, supervisor data, supervisor data, student guardian data, student data, and printable reports with the aim of providing fast and easy information in archiving.